H_âˆž state feedback for linear systems with decentralized control inputs - Helisyah Nur Fadhilah; Guisheng Zhai; Dieky Adzkiya; Erna Apriliani (SCIENCE NATURE, 2019)
This paper considers state feedback with decentralized structure for interconnected systems. The connection between subsystems is described by a directed graph. To design a decentralized controller, we use the information from its own subsystem and other subsystems based on the interconnection. Decentralized controller is defined as a solution of bilinear matrix inequality (BMI) problem, which is then solved by using the homotopy approach. Two numerical examples are performed to show validity of the design procedure